Hubungan Dukungan Keluarga Dengan Tekanan Darah Pada Pasien Hipertensi Di Wilayah Kerja Puskesmas Pintu Padang Kecamatan Batang Angkola - Simamora, Febrina Angraini; Lubis, Akriman Muslihul Anwar; ., Siti habibah (Universitas Aufa Royhan, 2016)
According to WHO (World Health Organization) , (2013) Hypertension affects one billion people worldwide. It is estimated that , in 2025 soared to 1.5 billion people . Based on basic medical research in 2009 states , the prevalence of hypertension in Indonesia at the age of 18 years and above by 31 % .This study aims to determine relationship of family support with blood pressure in hypertension patients in hutatonga region work in pintu padang public health center of batang angkoladistrict 2016. Design of this research is Descriptive Correlational with Cross Sectional approach. The sampling technique used muthade Solvin formula , and obtained 40 respondents. Data collection using questionnaires , questionnaires to measure family support experienced and observation method to determine the development of blood pressure . This questionnaire has been tested for validity and reliability . Analysis of the data by univariate and bivariate analysis with a significance level of 0.05 . The results of this study indicate that family support is yes 52.5 % , while the results of blood pressure is effective 13 people ( 32.5 % ) , and ineffective 16 ( 40.0 % ). Conlusion of respondents who suffered from severe hypertension as many as 11 people (27.5%). Chi square test results show the value and p < α is 0.05 ( 0.05 < 0.05 ) , which means that there is a relationship with the family support blood pressure in hypertensive patients .